2017
DOI: 10.1016/j.jfs.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Dating systemic financial stress episodes in the EU countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 33 publications
1
90
0
1
Order By: Relevance
“…. Quarterly country-level index of Þ nancial stress was calculated as a simple average of monthly levels of the country-level index of Þ nancial stress as developed and calculated by Duprey et al (2015); this index is constructed to reß ect volatility in three Þ nancial market segmentsequity market, bond market and foreign exchange market (see Duprey et al (2015) Observing the Þ gures, the heterogenous dynamics of the observed variables becomes evident. Application of regression estimation methods that account for heterogeneity is therefore well-suited.…”
Section: Data and The Empirical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…. Quarterly country-level index of Þ nancial stress was calculated as a simple average of monthly levels of the country-level index of Þ nancial stress as developed and calculated by Duprey et al (2015); this index is constructed to reß ect volatility in three Þ nancial market segmentsequity market, bond market and foreign exchange market (see Duprey et al (2015) Observing the Þ gures, the heterogenous dynamics of the observed variables becomes evident. Application of regression estimation methods that account for heterogeneity is therefore well-suited.…”
Section: Data and The Empirical Resultsmentioning
confidence: 99%
“…In countries more affected by the economic and Þ nancial market stress episodes, including Greece, Ireland, Italy, Portugal, and Spain, the drop in house prices has been more pronounced. The latter group of countries also experienced a sharper deterioration of macroeconomic activity 3 than the Þ rst group of countries and a "systemic Þ nancial stress that expanded beyond global Þ nancial crisis" (Duprey et al, 2015). Ample international empirical evidence (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the two financial stability indexes employed so far rely on the same logic for their calculation, we also estimate the trilemma indicator by employing a different Duprey et al (2015). This indicator is obtained on the basis of the stress on three financial market segments (equity, bond and foreign exchange rate) by using two variables for each segment.…”
Section: Alternative Financial Stability Indicatorsmentioning
confidence: 99%
“…To do so, we include the Country-level index of Financial Stress (CLIFS) as a covariant in the MS-AR model. This index measures the uncertainty in market prices by identifying simultaneous financial market turmoil across different assets (see Duprey et al 2017 for more details). 19 Finally, the ESI responses are not revised ex-post as most macroeconomic aggregates.…”
Section: Seriesmentioning
confidence: 99%